PENGARUH MODEL PEMBELAJARAN SCRAMBLE TERHADAP HASIL BELAJAR SISWA PADA SUBTEMA PENGARUH KALOR TERHADAP KEHIDUPAN KELAS V PADA PEMBELAJARAN SD NEGERI PERCONTOHAN - Seravina Sitinjak; Lisbet Novianti Sihombing; Hetdy Sitio (STAI Darul Qalam Tangerang, 2025)
The purpose of this study is to find out the Influence of the Scramble Learning Model on Student Learning Outcomes in Subtheme 3 Class V The Influence of Heat on Life in Pematangsiantar Pilot State Elementary School.This research is a quantitative research with a Pre-Experimental Design type with a One Group Pretest-Posttest research design (Initial Test-Final Test in a single group). In this study, only one research class was used, the sample of this study was class V which amounted to 30 students with the sampling technique using saturated sampling is a sample determination technique if the population is used as a sample. Based on the results of data analysis and hypothesis tests that have been carried out, the influence of the Scramble learning model on student learning outcomes. It can be seen that the acquisition of a significant value (2-tailed) is smaller than 0.05 (0.00<0.05) and the value of the tcount is greater than the ttable (13.152 > 2.048.), then H0 is rejected and Ha is accepted. So it can be concluded that the Scramble learning model has an effect on student outcomes in grade III subtheme 1 of SD Negeri Perpilotan.